ANALYSIS OF KEBON SIMBAH HYDROPONIC POSITIONING IN SURAKARTA CITY - Saputra , Raka Eka; Setiyani , Rahmawati; Sepfrian , Bimoseno (LPPM Universitas Duta Bangsa Surakarta, 2023)
This study aims to determine the positioning of Kebon Simbah Hydroponics in Surakarta City. This study used 36 respondents who prescribed purposive sampling. The research data were analyzed using multidimensional scaling (MDS) analysis. The results showed that the direct competitors of Kebon Simbah Hydroponics were Valefarm Hydroponics and Vegetable Hydroponics 04. Kebon Simbah Hydroponics based on positioning is in second place because Kebon Simbah Hydroponics has two advantages, namely price and service to consumers. The first place is occupied by Valefarm hydroponics because there are three advantages, namely taste, product quality and product availability, the third or last position is occupied by Vegetable Hydroponics 04 because Vegetable 04 hydroponics only has one advantage, namely in product packaging.